The Environmental Impact on the Development of the EU - Chankov, Georgi (Research Papers, 2012)
The European Union is a complex open system, put to a new kind of external pressure after 1989. The system approach gives us the possibility to foresee the further development though examining the interaction between the Union and its environment. The dynamic environment determines the external borders of the Union and raises the requirements towards its governance. Too manifold is influence of the external factors: partners and competitors (the USA, Japan, China and Russia), dependent regions in Eastern Europe and Northern Africa, the international institutional frame work (the WTO) and the Multinational companies. In this uncertain environment the Union moves towards a flexible scheme with center and periphery. The integration is not an act, but a process of reproduction of a community with variable interests and constant values and goals.